Spinal diffusion tensor imaging: A comprehensive review with emphasis on spinal cord anatomy and clinical applications. Issue 1 (4th February 2014) - Hendrix, Philipp; Griessenauer, Christoph J.; Cohen‐Adad, Julien; Rajasekaran, Shanmuganathan; Cauley, Keith A.; Shoja, Mohammadali M.; Pezeshk, Parham; Shane Tubbs, R.
<x xml:space="preserve">Abstract</x> Magnetic resonance imaging technology allows for in vivo visualization of fiber tracts of the central nervous system using diffusion‐weighted imaging sequences and data processing referred to as "diffusion tensor imaging" and "diffusion tensor tractography." While protocols for high‐fidelity diffusion tensor imaging of the brain are well established, the spinal cord has proven a more difficult target for diffusion tensor methods. Here, we review the current literature on spinal diffusion tensor imaging and tractography with special emphasis on neuroanatomical correlations and clinical applications. Clin. Anat. 28:88–95, 2015. © 2014 Wiley Periodicals, Inc.